IKATAN ALUMNI USM SUMATERA UTARA AND PPA ORGANISED ICEST 2016 - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, June 2016 – The success of the recently concluded International Conference of Computer, Environment, Social Science and Technology (ICEST 2016) jointly organised for the first time by University of Sumatera Utara (USU), Universiti Sains Malaysia (USM) Centre for Alumni Liaison (PPA) and Ikatan Alumni Sumatera Utara has paved the way for more such activities to be organised at the international level in the near future.